PENGARUH KEJELASAN SASARAN ANGGARAN, KETERLIBATAN KERJA, BUDGET EMPHASIS, PARTISIPASI ANGGARAN, ASIMETRI INFORMASI TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (STUDI PADA OPD PROVINSI RIAU) - Wiry Widyawati.S; Kirmizi Kirmizi; Novita Indrawati (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
The purpose of this study was to find out the influence of clarity of budget objectives,job engagement, budget emphasis, budget partisispation, and informationasymmetry on budget slack. And whether organizational commitment can moderatethe relationship between clarity of budget objectives, work engagement, budgetemphasis, participation budget, and information asymmetry. This research wasconducted at 34 OPD of Riau Province Government, each agency was given 5Questionnaires addressed to Echelon II, Echelon III, and Echelon IV, 45 people. Themethod of data collection is to use the questionnaire list. While the method of dataanalysis using multiple analysis and Moderated Regression Analysis (MRA) usingtools SPSS. The results show that budget goal clarity, job involvement, budgetemphasis, budget participation, and information asymmetry influence on budgetslack. then the organizational commitment can strengthen the relationship betweenclarity of budget objectives, work engagement, budget emphasis, participationbudget, and information asymmetry of budget fight.